DEVELOPMENT OF RILIS MODEL (CRITICAL LITERACY BASED INQUIRY) ON READING-WRITING LEARNING IN COLLEGE - Akhiruddin; Ramly; Syamsudduha; Sahabuddin, Romansyah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aims to develop the RILIS (Critical Literacy-Based Inquiry) Model in reading-writing learning in higher education, which is designed to improve students' literacy skills, especially in writing academic essays. This model was developed using a research and development approach with the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) framework. The subjects of the study were lecturers and students of the Indonesian Language Education Study Program, University of Papua. The results of the study indicate that the RILIS Model has high validity based on expert testing, practicality assessed through field trials, and effectiveness proven through pretest-posttest analysis (Asymp. Sig. = 0.01 < 0.05). This model integrates critical literacy with reading-writing learning, including eight main components: orientation, syntax, reaction principles, social systems, and learning impacts. The use of the RILIS Model has been proven to significantly improve students' writing skills, especially in compiling critical and structured academic essays. This study concludes that the RILIS Model is a valid, practical, and effective learning innovation to be applied in higher education. This model is expected to be a guide for lecturers in integrating reading and writing learning based on critical literacy, while also contributing to improving student literacy in Indonesia